Relationship between serum thyroid hormone and IL-1β levels and postmortem tissue deiodinase activity in critically ill patients - Zhong, ZhenZhou; Xiao, XiaoLiu (Journal of Medical Biochemistry, 2024)
Objective: This study investigated the relationship between serum thyroid hormones and IL-1β levels and postmortem tissue deiodinase activity in critically ill patients. Methods: Serum thyroid hormones and IL-1β were measured on the 5th, 15th, and last day of 80 critically ill patients. Forty of these patients were non-survived, and liver and skeletal muscle were harvested to analyze deiodinase activity. Results: Serum TSH, T4, and T3 were decreased, and rT3 and IL-1β were increased in non-survivors. From day 5 to the last day, serum TSH, T4, and T3 levels increased, and rT3 and IL-1β levels decreased with time in survivors, while serum TSH, T4, and T3 levels decreased or remained unchanged, and rT3 and IL-1β increased in non-survivors. On the last day, liver D1 activity was in a negative correlation with serum rT3 and IL-1β, while liver and skeletal muscle D3 activities were in a positive correlation. Conclusion: Serum thyroid hormones and IL-1β are correlated with postmortem deiodinase activity in critically ill patients.